Church and civil society: German and South African perspectives - Welker, Michael; Koopman, Nico; Vorster, J. M. (SUN PRESS, 2017)
The originality of the volume is in the comparative and multi-facetted approach to a contemporary ethical problem of global proportions facing churches and faith-based organisations as well as civil society bodies in Germany and South Africa. Apart from the topicality of the social and political issues under discussion, the value of this volume lies in the intellectual stringency and honesty of the contributors in dealing with its central concern: finding and defining an ethical discourse for Christians in a fractured society, a responsible practical theology in the face of an increasingly secular and apathetic world. Its strength is the wide range of issues dealt with and the different viewpoints that are represented. The contributions reflect the current situation and intellectual debates in both Germany and South Africa, and range from Biblical exegesis and the implications of the injunction to seek "first the Kingdom" to specific topics such as the role of NGOs, the South African Council of Churches or liberation theology, also health care or the anti-corruption dialogue, or the condition of being a stateless refugee, and the meaning of the mission today